Dissecting protein-protein interactions facilitating secretion of the virulence factor EspC by enteropathogenic Escherichia coli - Bishop, Keith (2009)
This study investigates the domain structure and secretion of the autotransporter (AT) EspC, secreted by enteropathogenic Escherichia coli (EPEC). The boundaries of the archetypical signal peptide and beta-domain surrounding the passenger domain of EspC were established. Then, structural modelling was used to define a region of EspC between the passenger- and β-domains, termed the inter-domain, which may comprise a passenger- chaperone domain. Yeast two-hybrid and co-purification approaches were subsequently used to assess protein-protein interactions between individual EspC domains and with a putative secretion accessory factor, YbgC. Direct interaction between the EspC passenger- and inter-domain was observed, consistent with a proposed chaperone function for the inter-domain. Structural modelling identified conserved surface motifs within the inter-region as targets for mutagenesis to determine their influence upon EspC secretion. Complementation of an EPEC espC mutant strain with inter-domain EspC mutants showed profound affects on secretion. Furthermore, these mutants had a dominant-negative affect on wildtype EspC secretion, affecting bacterial cell viability.